Transcriptional regulations of pollen tube reception are associated with the fertility of the ginger species Zingiber zerumbet and Zingiber corallinum - Liang, Shan; Hu, Ming-li; Lin, Hao-chuan; He, Han-jun; Ning, Xi-ping; Peng, Pei-pei; Lu, Guo-hui; Sun, Shu-lan; Wang, Xiao-jing; Wang, Ying-qiang; Wu, Hong (Frontiers in Plant Science, 2023)
Zingiber zerumbet and Zingiber corallinum are economically valuable species in the genus Zingiber. While Z. corallinum is sexually active, Z. zerumbet adopts clonal propagation, although it has the potential for sexual reproduction. It is unclear so far at which step during the sexual reproduction of Z. zerumbet inhibition occurs, and what are the regulatory mechanisms underlying this inhibition. Here, by comparing with the fertile species Z. corallinum using microscopy-based methods, we show that rare differences were observed in Z. zerumbet up to the point when the pollen tubes invaded the ovules. However, a significantly higher percentage of ovules still contained intact pollen tubes 24 h after pollination, suggesting pollen tube rupture was impaired in this species. Further RNA-seq analysis generated accordant results, showing that the transcription of ANX and FER, as well as genes for the partners in the same complexes (e.g., BUPS and LRE, respectively), and those putative peptide signals (e.g., RALF34), were timely activated in Z. corallinum, which ensured the pollen tubes being able to grow, reorient to ovules, and receipt by embryo sacs. In Z. zerumbet, genes for these complexes were cooperatively suppressed, which would result in the maintenance of PT integrity due to the disruption of RALF34-ANX/BUPS signaling in PT and the failure of PT reception by an active synergid due to the insufficiency of the synergid-harbored FER/LRE complex. Taking the results from the cytological and RNA-seq studies together, a model is proposed to illustrate the possible regulation mechanisms in Z. zerumbet and Z. corallinum, in which the regulations for pollen tube rupture and reception are proposed as the barrier for sexual reproduction in Z. zerumbet.